Streptococcus and related oral taxa are differentially abundant in patients with abdominal aortic aneurysms compared with atherosclerotic disease controls - Joshua T. Geiger; Ann L. Gill; Mario Matabele; Joel Kruger; Baqir Kedwai; Daniel Lehane; Benjamin Ford; Michael C. Stoner; Michael B. Sohn; Steven R. Gill; Doran Mix (Frontiers in Cardiovascular Medicine, 2026)
Objective Bacterial DNA from oral microorganisms has been found in various cardiovascular tissues, including abdominal aortic aneurysm (AAA) tissue. In addition, experiments in murine models have shown that the oral pathogen Porphyromonas gingivalis can independently contribute to aneurysm formation. However, whether the oral microbial community differs between patients with AAA and those with advanced atherosclerotic disease remains unknown. This study tests the hypothesis that specific bacterial taxa are differentially abundant in patients with AAA compared to those with advanced atherosclerotic disease. Methods A total of 73 oral wash samples were collected from 45 subjects with AAA and 28 with atherosclerotic disease. Bacterial DNA was isolated, and the V1-V3 segment of the bacterial 16S rRNA gene was amplified. Taxonomic profiles were constructed using DADA2, and statistical inferences on alpha diversity, beta diversity, and differential abundance were performed, adjusting for age, sex, smoking status, and cancer history. Sensitivity analyses additionally adjusted for cancer status, statin use, proton pump inhibitor use, and diabetes. Bacterial gene potential functions were predicted using PICRUSt2. Results The oral microbial community composition differed in beta diversity (weighted UniFrac distance, R = 0.166, p < 0.001) and trended towards a difference in alpha diversity (Shannon index, p = 0.054) between patients with AAA and advanced isolated atherosclerotic disease. Ten bacterial taxa are overabundant in patients with AAA compared with those with atherosclerotic disease, most notably the genus Streptococcus (log2 fold change: 2.06, p = 0.002). PICRUSt2 predicted bacterial pathways related to protein synthesis and DNA replication that were likely to be less abundant, and pathways related to bacterial motility that were likely to be more abundant in oral cavity bacteria in subjects with AAA. Conclusions These findings demonstrate that the oral microbiome differs between patients with AAA and those with advanced atherosclerotic disease and support further investigation of oral microbial alterations and their relationship to vascular pathologies. The known link between Streptococcus and cardiovascular disease makes these results particularly intriguing. Further multi-omic studies with greater power may identify bacterial species and proteins that correlate with disease presence and progression.